Clinical and Neurophysiological Features of Hereditary Motor sensory Neuropathy, Issues of Optimization of Diagnosis and Therapy (Eurasian Medical Research Periodical, 2022)
Hereditary neuropathies are a group of severe genetic heterogeneous diseases of the peripheral nervous system, characterized by pronounced clinical polymorphism. Currently, it is customary to distinguish 4 groups of neuropathy depending on the combination of damage to the motor or sensory portions of the peripheral nerves, and the most common group is NMSN. They account for about 80% of all patients, which are divided into two main types: demyelinating (1) and axonal (2). All HMSN groups were characterized by a triad of clinical symptoms: atrophy of the distal parts of the hands and feet with their deformity, sensory disturbance in the area of atrophied muscles, hypo or areflexia of the muscles of the upper and lower extremities